Tinjauan Umum Tentang Wali Nikah - Muhammad Lutfi Syarifuddin (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2018)
Judging from the root of the language, the word guardian comes from Arabic which means protector, guarantor (someone's life). While the word